2009
DOI: 10.1016/j.virol.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variability and genetic structure of the population of Soybean mosaic virus based on the analysis of complete genome sequences

Abstract: The complete genomes of 30 Soybean mosaic virus (SMV) isolates and strains were sequenced in this study. Together with fourteen previously reported sequences, we analyzed the genetic structure of the SMV population. Analyses of genetic diversity showed that different genomic regions of SMV are under different evolutionary constraints and that there was no significant genetic differentiation between East Asian and North American populations of SMV. Phylogenetic analyses revealed a significant correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
85
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 56 publications
12
85
2
1
Order By: Relevance
“…This genomic region has also been recently detected as hotspot for recombination in several other members of potyvirus such as Sweet potato feathery mottle virus [22], Soybean mosaic virus (SMV) [23], and Watermelon mosaic virus [24]. Taken together with the previous studies [2,11,12,14,25], this study has also revealed that recombination is the major driving force in the emergence of new variants of SCMV.…”
supporting
confidence: 69%
“…This genomic region has also been recently detected as hotspot for recombination in several other members of potyvirus such as Sweet potato feathery mottle virus [22], Soybean mosaic virus (SMV) [23], and Watermelon mosaic virus [24]. Taken together with the previous studies [2,11,12,14,25], this study has also revealed that recombination is the major driving force in the emergence of new variants of SCMV.…”
supporting
confidence: 69%
“…Phylogenetic analysis did not indicate a clear relationship between genetic variability of BBrMV isolates and their geographical origin. Seo et al [19] reported that the phylogenetic trees were inconsistent and did not support geographic clustering of the Soybean mosaic virus (SMV) isolates. The phylogenetic inconsistency and clustering pattern in BBrMV isolates might be due to the movement of infected suckers across the districts of Tamil Nadu and other states in south India.…”
Section: Discussionmentioning
confidence: 99%
“…They have spread throughout much of the subtropical and temperate zones of the world King et al, 2012). Potato virus Y (Ogawa et al, 2008;Visser et al, 2012), turnip mosaic virus (TuMV) (Ohshima et al, 2002), soybean mosaic virus (Seo et al, 2009) and zucchini yellow mosaic virus (Lecoq et al, 2009) are important potyviruses with worldwide distributions. Nevertheless, there remains a poor understanding of how and when they dispersed, and of what factors controlled that spread.…”
Section: Introductionmentioning
confidence: 99%